2004
DOI: 10.1007/s00223-002-0021-1
|View full text |Cite
|
Sign up to set email alerts
|

Uni-axial Cyclic Stretch Induces Cbfa1 Expression in Spinal Ligament Cells Derived from Patients with Ossification of the Posterior Longitudinal Ligament

Abstract: Ossification of the posterior longitudinal ligament of the spine (OPLL) is characterized by ectopic bone formation in the spinal ligaments. Mechanical stress, which acts on the posterior ligaments, is thought to be an important factor in the progression of OPLL. To clarify this mechanism, we investigated the effects of in vitro cyclic stretch (120% peak to peak, at 0.5 Hz) on cultured spinal ligament cells derived from OPLL (OPLL cells) and non-OPLL (non-OPLL cells) patients. The mRNA expressions of Cbfa1 (an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Fibroblasts cells can differentiate into osteoblasts or osteocytes [4,8,9,12,24,28]. This differentiation should be accompanied by an upregulation of several marker genes related to bone formation, such as OCN, ALP and COL I.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibroblasts cells can differentiate into osteoblasts or osteocytes [4,8,9,12,24,28]. This differentiation should be accompanied by an upregulation of several marker genes related to bone formation, such as OCN, ALP and COL I.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to simulate the mechanical stress in vitro, mostly with a motor-driven uniaxial sinusoidal cyclic stretch [18]. The system induced the transcription of messenger ribonucleic acids of several growth factors, including BMP-2, BMP-4, prostaglandin I 2 synthase, and osteoblast-specific transcription factor in the cells from OPLL patients [9,19,24,30]. At the same time, several studies have suggested that ER stress response can be activated by mechanical stress in some cellular pathological processes, such as apoptosis in rat annulus fibrosus cells or human connective tissue cells [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in patients that underwent anterior interbody fusion, the development of ossification evidently slowed and even stopped [17]. Based on these reports, OPLL may tend to progress at the area where mechanical stretch exists, which has been reported by several authors [5,6,18].…”
Section: Discussionmentioning
confidence: 73%
“…OPLL is a chronic and progressive disease, and clinical symptoms may only occur after the ossified ligaments develop to a certain degree. Although some studies have investigated the role of mechanical strain in OPLL development, the signaling mechanism of such a role remains unclear [5,6].…”
Section: Introductionmentioning
confidence: 99%